Techno-Economic Analysis of the Business Potential of Recycling Lithium-ion Batteries Using Hydrometallurgical Methods - Rachmadhani, Dwi Rizky; Priyono, Bambang (Bumi Publikasi Nusantara, 2024)
Indonesia is committed to achieving net zero emissions by 2060 through short-term policies. The focus includes energy efficiency, renewable resources in the electricity sector, and transportation electrification. Transportation electrification leads to increased use of lithium-ion batteries, predicted to grow at a CAGR of 25.45%. The installed capacity of lithium-ion batteries is expected to reach 10.5 TWh, with 8.1 TWh in electric vehicles by 2030. The waste from lithium-ion batteries in Indonesia is estimated to be 250,000 tons by 2020, increasing with electric vehicle policies. By 2040, it is projected to require 0.2 million tons of cobalt and 1.3 million tons of nickel. Recycling support to address domestic lithium unavailability results in a circular economy worth US 49,767,416 and reduces emissions by 7,472 tons of CO2 from devices sold in 2022.